1990
DOI: 10.1002/cne.902960408
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneus trunci muscle reflex of the guinea pig

Abstract: The cutaneus trunci muscle reflex in guinea pigs was studied with a combination of video analysis, electromyography, lesioning, and light microscopy. The muscle forms a bilateral, subdermal sheet over much of the trunk. Local contractions of the dorsal part of the muscle are produced in response to brief tactile or electrical stimulation of the skin and consist of a twitch centered 1-2 cm rostral of the stimulus site. The reflex receptive field covers most of the thoracic and lumbar dorsal surface. The sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 42 publications
3
63
1
Order By: Relevance
“…In guinea pigs, it has been shown that the twitch response does not readily habituate or fatigue at stimulus frequencies below 10 Hz [3]. Similarly, isolated rat m. cutaneus trunci continues to contract in response to repeated electrical stimulations over a period of several hours [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In guinea pigs, it has been shown that the twitch response does not readily habituate or fatigue at stimulus frequencies below 10 Hz [3]. Similarly, isolated rat m. cutaneus trunci continues to contract in response to repeated electrical stimulations over a period of several hours [24].…”
Section: Discussionmentioning
confidence: 99%
“…M. cutaneus trunci has been described in detail in the cat [9], dog [9,10], and guinea pig [3]. However, descriptions of the equine m. cutaneus trunci are inconsistent in terms of its size and shape, especially the dorsal profile that extends toward the panels of the saddle and the orientation of its fibers [1,2,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore likely that 4-Cl-3-HAA has a longer therapeutic window than MP, because the peak of QUIN accumulation does not occur until 12 days after injury. 25 These indications should [26][27][28] be considered when and if therapeutic interventions targeting QUIN accumulation are tested clinically.…”
Section: Discussionmentioning
confidence: 99%
“…One may conclude that forelimb function (and supraspinal function in general) can be significantly affected by more caudal spinal lesions, and this factor should be taken into consideration in evaluating recovery. Indeed, the cutaneous trunci muscle reflex provides a mechanism for transmitting information across the lesion site extraspinally, since the trunk muscles can be controlled from above the lesion while the sensory response to muscle contraction would enter below the lesion (Blight et al, 1990). It has been established that increasing general sensory input to the spinal cord can facilitate descending activation of motoneurons (Dimitrijevic, 1988).…”
Section: Contributions Of Cutaneous Trunci Muscle Activity To Asr Andmentioning
confidence: 99%